Angiotensins and Huntington’s Disease: A Study on Immortalized Progenitor Striatal Cell Lines - De Mello, Walmor C.; Gerena, Yamil; Ayala-Peña, Sylvette (Frontiers in Endocrinology, 2017)
Neurons from mouse models of Huntington’s disease (HD) exhibit altered electrophysiological properties, potentially contributing to neuronal dysfunction and neurodegeneration. The renin–angiotensin system (RAS) is a potential contributor to the pathophysiology of neurodegenerative diseases. However, the role of angiotensin II (Ang II) and angiotensin (1-7) has not been characterized in HD. We investigated the influence of Ang II and angiotensin (1-7) on total potassium current using immortalized progenitor mutant huntingtin-expressing (Q111) and wild-type (Q7) cell lines. Measurements of potassium current were performed using the whole cell configuration of pCLAMP. The results showed that (1) the effect of Ang II administered to the bath caused a negligible effect on potassium current in mutant Q111 cells compared with wild-type Q7 cells and that intracellular administration of Ang II reduced the potassium current in wild type but not in mutant cells; (2) the small effect of Ang II was abolished by losartan; (3) intracellular administration of Ang II performed in mutant huntingtin-expressing Q111 cells revealed a negligible effect of the peptide on potassium current; (4) flow cytometer analysis indicated a low expression of Ang II AT1 receptors in mutant Q111 cells; (5) mutant huntingtin-expressing striatal cells are highly sensitive to Ang (1-7) and that the effect of Ang (1-7) is related to the activation of Mas receptors. In conclusion, mutant huntingtin-expressing cells showed a negligible effect of Ang II on potassium current, a result probably due to the reduced expression of AT1 receptors at the surface cell membrane. In contrast, administration of Ang (1-7) to the bath showed a significant decline of the potassium current in mutant cells, an effect dependent on the activation of Mas receptors. Ang II had an intracrine effect in wild-type cells and Ang (1-7) exerted a significant effect in mutant huntingtin-expressing striatal cells.